Relationship Between Cerebroplacental Ratio and Fetal Outcome Among Women with Preeclampsia in Irrua, Edo State, Nigeria - Olugbenga, O E; Momoh, M O; Omorogbe, F I; Okome, G B O; Isabu, P A; Olugbenga, M A; Eigbefoh, J O; Alikah, S O (British Journal of Healthcare and Medical Research, 2025)
Background: Fetal Doppler ultrasound scan has become a quick way of screening for fetal compromise and determining appropriate management in high-risk pregnancies such as preeclampsia. The role of cerebroplacental ratio for this purpose is being explored. Aim: The aim of this study is to evaluate the relationship between cerebroplacental ratio and fetal outcome among women with preeclampsia. Methodology: This prospective cohort study was among 100 consecutive women with singleton pregnancies and preeclampsia between 34weeks and 37 weeks of gestation, recruited for umbilical and middle cerebral artery Doppler with the cerebroplacental ratio (CPR) determined. Statistical analysis was performed using SPSS 23.0, with significance set at p < 0.05. Results: Among them, 19% had pathologic CPR of <1 while 81% had normal CPR. The APGAR scores were significantly lower among those with pathologic CPR in the first minute (X2꞊40.443, df꞊2, P<0.001) and fifth minute (X2꞊17.311, df꞊2, P<0.001) respectively. Out of those admitted in the special care baby unit(SCBU), 62.1% had abnormal CPR while 37.9% had normal CPR(X2꞊49.23, df꞊1, P<0.001). One intrauterine fetal death occurred in each group and of the cases of Early Neonatal Death (ENND), 5(83.3%) had abnormal CPR and 1(16.7%) had a normal CPR which was statistically significant (X2꞊14.118, df꞊2. p꞊0.001). Conclusion: A significant relationship between CPR and adverse perinatal outcome exists, in terms of low APGAR scores, SCBU admission and perinatal mortality in neonates of women with preeclampsia with no significant difference in the mode of delivery.